1996
DOI: 10.1042/cs0900073
|View full text |Cite
|
Sign up to set email alerts
|

Bed Rest Decreases Whole-Body Protein Turnover in Post-Absorptive Man

Abstract: 1. Whole-body protein turnover was measured using the [15N]glycine tracer technique in 10 post-absorptive healthy volunteers during normal daily activities and a period of bed rest. 2. Bed rest reduced whole-body protein turnover (25%), synthesis (26%) and breakdown (25%), but short-term urinary nitrogen excretion remained unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Results from the current study could be different from existing literature because ingestion of extra dietary PAA may not effectively alter the physiological changes in the body that are induced by muscle unloading. It is suggested that amino acid catabolism and whole body protein turnover is upregulated during unloading and immobilization [2], and in as little as 14 days of bed rest whole body protein turnover decreases by 15%, with 50% of the decrease coming from an attenuation of protein synthesis [29]. Research also indicates that during unloading and disuse conditions, the decrease in protein synthesis appears to drive the loss of muscle mass, while the rate of protein degradation remains fairly constant [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Results from the current study could be different from existing literature because ingestion of extra dietary PAA may not effectively alter the physiological changes in the body that are induced by muscle unloading. It is suggested that amino acid catabolism and whole body protein turnover is upregulated during unloading and immobilization [2], and in as little as 14 days of bed rest whole body protein turnover decreases by 15%, with 50% of the decrease coming from an attenuation of protein synthesis [29]. Research also indicates that during unloading and disuse conditions, the decrease in protein synthesis appears to drive the loss of muscle mass, while the rate of protein degradation remains fairly constant [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…With bed rest alone, whole body measurements are largely reflective of skeletal muscle changes [8]. Whole body protein turnover decreases in as little as 9 h of inactivity [17], and integrated measures over 24 h that include nutrient intake confirm net muscle catabolism with acute inactivity [18]. Whole body protein turnover decreases after 7 [19] and 14 days [8,20] of bed rest as a result of a decrease in protein synthesis.…”
Section: Inactivity and Muscle Protein Metabolismmentioning
confidence: 99%
“…Unfortunately, a degree of muscular inactivity is inevitable in many situations, including convalescence from illness or injury, exposure to microgravity, and the progression of aging. Mechanistically, the loss of lean body mass associated with prolonged bedrest is primarily due to alterations in protein turnover (1), including an increase in protein degradation and/or a decrease in protein synthesis (2)(3)(4). In each instance, the resultant muscle atrophy is most pronounced in the muscles of the lower back and legs (5)(6)(7)(8).…”
mentioning
confidence: 98%